Electronic structure of antistructure Co atoms and Co vacancies in CoAl - N. Stefanou; R. Zeller; P.H. Dederichs (Solid State Communications, 1986)
We report on self-consistent ab-initio calculations for the electronic structure of intrinsic defects in CoAl, i.e. antistructure (AS) Co atoms and vacancies on the Co sublattice. The calculations are based on the Korringa-Kohn-Rostoker (KKR) Green's function method and employ the local spin density approximation of the density functional theory. The results for the densities of states, the charge transfers and the local moments are discussed and compared with the available experimental data.